15y-6=11

Simple and best practice solution for 15y-6=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15y-6=11 equation:


Simplifying
15y + -6 = 11

Reorder the terms:
-6 + 15y = 11

Solving
-6 + 15y = 11

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 15y = 11 + 6

Combine like terms: -6 + 6 = 0
0 + 15y = 11 + 6
15y = 11 + 6

Combine like terms: 11 + 6 = 17
15y = 17

Divide each side by '15'.
y = 1.133333333

Simplifying
y = 1.133333333

See similar equations:

| 8-5+j=67 | | 9y=3y | | 25w^2-x^2=0 | | -12+8m-6+1=1+5m+6m | | -12+8m-6+1=1+5m+6 | | -286+88= | | 1=x-1 | | 6r^3+15r^2-6r= | | 6y^2+3y-18=0 | | -10+8k=3k-5 | | 2x+4(0)=8 | | x=4x+12 | | 8-2(x+5)=4(2x-1) | | 5x-1=4x+9 | | 8(5n+7)=216 | | 4=p-2 | | -5+x=-3 | | 16=4a+8+4a | | 6x+4=2(x-6) | | 8a^2-4d=60 | | 15x-7x=-52-5x | | 12x^2-33x+18=0 | | 8y^2+26y=-15 | | 5m+1-8m=22 | | 1m/9+10=16 | | M+4=20+3m | | 10x-35=5x+25 | | 3(4k+8)-2(2k+3)-14k= | | 8(y-5)=6y-19 | | 3x-9=x+15 | | 67*2(56+6)-(-7+7)= | | -7x+4x+15-8x= |

Equations solver categories